Słuchowisko dokumentalne a rzeczywistość - Bachura-Wojtasik, Joanna (Zagadnienia Rodzajów Literackich, 2021)
The article attempts to classify documentary radio-play. The research material came from 2001–2019 and included radio-plays, which were produced in the Polish Radio Theatre and in the sixteen regional Polish Radio stations, presented during the Two Theaters Festival in Sopot. The author used a quantitative and qualitative method of analyzing the medium content. The number of documentary radio-plays in relation to the number of all radioplays presented during the Two Theaters Festival in 2001–2019, then the percentage ratio of the three categories of documentary radio-plays and the percentage ratio of documentaryplays from the Polish national radio stations and regional radio stations are presented in the charts prepared by the author. In deliberating on the essence of the documentary radio-plays the author posed the following research questions: what is the interest of the authors in documentary radio-plays in relation to other radio-plays in the last twenty years?; what kind of topics are the most interested for the authors?; what historical events are reflected in the radio plot?; do artists critically review the past?; what is the formal structure of documentary radio-plays?; do the authors reach for reporter’s recordings?; and finally — what formal and compositional procedures do the creators use to influence the audiences’ involvement? However, the attitude to reality in the discussed documentary radio-plays allowed the author to divide them into the following categories: firstly — these are radio-plays based on documents, memoirs, letters, archival materials; secondly — radio plays based on documents, memories, letters, archival materials but enriched with contemporary reporter’s materials, conversations with real characters; thirdly — radio-plays about history, events, authentic characters, in which the past is the starting point for telling the author’s story.